THE IMPORTANCE OF AMINO ACIDS IN GASTRIC DISEASES (International journal of artificial intelligence, 2025)
Aminoacids play an essential role in various biological processes, including protein synthesis, energy metabolism, and immune function. They also serve as precursors for the synthesis of neurotransmitters, hormones, and other vital compounds in the body. This article discusses amino acids, their structure, types, and their medical importance—particularly in gastric diseases—providing information about glutamine, glycine, histidine, and other amino acids.